Application of the AHP and PROMETHEE II methods to the evaluation of the competitiveness of Polish and Russian Baltic container terminals - Bartosiewicz, Aleksandra (Array, 2020)
The rapid growth in the volume of international container transport enforces the improvement of competitiveness in the entire transport chain, including maritime container terminals. Reports and scientific surveys on the Baltic Sea Region (BSR) tend to concentrate on annual results achieved by entire ports, largely ignoring the efficiency of individual terminals. The aim of the article is to fill this research gap and consequently examine the competitiveness of the most important maritime container terminals in Poland and their Russian competitors. To this end, selected Polish and Russian bases were examined with regard to a number of criteria, such as the length of the quay (c1), the number of RTG (c2) and STS (c3) cranes, the number of shortsea shipping connections (c4), the maximum depth at the quay (c5), the distance from motorways and expressways/national roads (c6) or the distance from the national railway station (c7). The above seven criteria were subsequently used to perform a strategic group mapping as well as AHP and PROMETHEE II multi-criteria rankings that enabled to specify those Baltic Sea container nodes which are in the area of strategic benefits for the analysed market sector. According to the results obtained, the Russian Petrolesport and the Polish DCT Gdańsk are the leaders of the market. This fact confirms their competitive advantage over other market players of the sector in question.